Work Motivation and Employee Performance With Organizational Citizenship Behavior as Moderating Variable: Survey of State Civil Apparatus (ASN) In Ponorogo Regency - Marjam Desma Rahadhini (CV. Inara, 2022)
This study aims to examine the effect of work motivation on the performance of ASN in Ponorogo Regency. In addition, this study also examines the role of the intervening variable Organizational Citizenship Behavior (OCB) in influencing the relationship between work motivation and performance. The population of this study were employees at the Ponorogo Regency Office with a total of 624 ASN, while the sampling technique used proportional random sampling with a percentage of 15 percent of the total population of 94 respondents. The results showed that job satisfaction had a significant effect on OCB in ASN in Ponorogo Regency, Job satisfaction had a significant effect on the performance of ASN employees in Ponorogo Regency. OCB has a significant effect on the performance of ASN employees in Ponorogo Regency and OCB mediates the effect of job satisfaction on the performance of ASN employees in Ponorogo Regency.